2003
DOI: 10.7326/0003-4819-139-8-200310210-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins on Nonlipid Serum Markers Associated with Cardiovascular Disease

Abstract: Among nonlipid serum markers examined, only C-reactive protein levels are statistically significantly affected by statins. These findings suggest that statin-mediated anti-inflammatory effects may contribute to the ability of statins to reduce risk for cardiovascular disease. Overall, however, available data are insufficient to support recommendations for using nonlipid serum markers in decisions regarding statin therapy for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
5
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 109 publications
7
103
5
7
Order By: Relevance
“…In 1998, investigators working in the Cholesterol and Recurrent Events (CARE) trial reported that the clinical benefit of statins in terms of event reduction was greater among those with increased CRP, and that statin therapy reduces CRP concentrations in a largely LDL-independent manner (33,34 ). These observations were subsequently confirmed for all statins (35)(36)(37)(38)(39), although more potent agents such as rosuvastatin appear to result in even greater LDL and CRP reductions. Thus, by 1999, evidence was rapidly accruing not only that CRP might represent a novel biomarker of vascular risk, but that CRP evaluation might also merit consideration as a method to monitor pharmacologic interventions used to prevent and treat cardiovascular disease.…”
Section: C-reactive Protein (Crp)supporting
confidence: 51%
“…In 1998, investigators working in the Cholesterol and Recurrent Events (CARE) trial reported that the clinical benefit of statins in terms of event reduction was greater among those with increased CRP, and that statin therapy reduces CRP concentrations in a largely LDL-independent manner (33,34 ). These observations were subsequently confirmed for all statins (35)(36)(37)(38)(39), although more potent agents such as rosuvastatin appear to result in even greater LDL and CRP reductions. Thus, by 1999, evidence was rapidly accruing not only that CRP might represent a novel biomarker of vascular risk, but that CRP evaluation might also merit consideration as a method to monitor pharmacologic interventions used to prevent and treat cardiovascular disease.…”
Section: C-reactive Protein (Crp)supporting
confidence: 51%
“…Moreover, statins, which inhibit the major rate limiting step of the mevalonate pathway, namely the conversion of HMGCoA into mevalonate, have consistently been shown to lower CRP. 27 Meanwhile, a recent study suggested that the contribution of the e4 allele towards lowering CRP levels is independent and may be by a different mechanism than how statins affect inflammation. 19 However, implication of lipoprotein pathway of the cholesterol transport remained plausible since Schwalbe et al 28 reported that CRP may be complexed with lipoprotein by a direct interaction with the apolipoprotein E molecule, suggesting a direct effect of the APOE e4 allele on hs-CRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs with a Fiblowering effect are angiotensin converting enzyme inhibitors (ACEI) [65], angiotensin receptor blockers (ARB) [66], -blockers [66,67] and ticlopidine [68]. Despite significant reductions sporadically reported in some pravastatin studies [69][70][71], Fib-lowering action of statins is disputable [72]. Studies on PAD patients showed that the use of vasodilators [73], rheological [74] and thrombolytic [75,76] agents leads to reduced Fib levels, usually accompanied by clinical improvement.…”
Section: Fib and Cvd Pathophysiologymentioning
confidence: 99%